Anticonvulsant pharmacotherapy for generalized and localized vulvodynia: a critical review of the literature. (2013) - Spoelstra, Symen K.; Borg, Charmaine; Weijmar Schultz, Willibrord C. M.
Abstract Anticonvulsant therapy has occasionally been recommended to treat vulvodynia. However, convincing evidence to support this therapeutic option is lacking. The goal of this study was to critically review studies published on the effectiveness of anticonvulsants for the treatment of vulvodynia. Evaluation of the methodological quality of relevant publications was the main outcome measure. MEDLINE, PubMED and Cochrane were used to identify studies published in English between January 1999 and February 2013. Searches were performed between December 2012 and February 2013. Articles were appraised with the Oxford Centre for Evidence-Based Medicine – Levels of Evidence. Eight relevant studies were identified: two case reports, three retrospective studies, two non-randomized prospective studies and one open-label pilot trial study. Gabapentin formed the main focus (87.5%) to reduce vulvar pain; success rates ranged from 50 to 82%. Lamotrigine was used in one study (12.5%) to relieve symptoms; satisfaction was reported in 82%. These results seem promising, but the majority of studies have several methodological weaknesses regarding sample size and design. Insufficient evidence was available to recommend anticonvulsants for the treatment of vulvodynia. Further studies are necessary with double-blind, randomized-controlled designs to investigate the effectiveness of anticonvulsant therapy for vulvodynia.